G373(P) The use of a low-dose prednisolone regimen to treat a relapse of childhood nephrotic syndrome. (7th April 2014) - Raja, K; Hothi, D; Webb, H
Abstract : Background: 70–80% of children with nephrotic syndrome develop relapses. These are typically treated with a course of high dose prednisolone and about half go on to develop frequently relapsing disease. Not only are the relapses associated with an increased risk of complications, their treatment with steroids is associated with major adverse effects including diabetes, hypertension and behavioural problems. In this retrospective review we wanted to see whether a lower dose of prednisolone could successfully treat a relapse in those children that were steroid sensitive, given the concerns regarding long-term steroid toxicity. Methods: We included any child with steroid sensitive nephrotic syndrome that presented with a relapse (3+ proteinuria for atleast 3 days) during January 2012 to July 2013 and was treated with a low-dose prednisolone regimen. These patients had been asked to take low dose prednisolone (</= 1 mg/kg) for a maximum of 7 days, and go up to the standard 2 mg/kg dose if there had not been any response in that time. Results: 43 patients were included in the study with a total of 79 episodes. Patients were between 3 and 17 years old (mean age 10.07 years). 55 of 79 patients (70%) responded within a week. 20 of 79 (25%) patients were on no medication at the time of relapse. Of the remaining, 40 (50%) were on alternate day prednisolone, with or without another agent (23 of 79 and 17 of 79 respectively). The remaining 19 (25%) were on 1 other agent. For those on alternate day prednisolone, the average dose was 0.32 mg/kg. We compared the mean number of relapses in the 6 months preceding the current relapse and the 6 months following (2.09 v 0.89). Using a paired t-test comparison of the means gave a p value of <0.0001. Conclusion: A significant proportion of patients (70%) responded to treatment of their relapse with a low-dose prednisolone regimen without any increase in the frequency of their relapses.